Results of use of fibrin glue for surgical treatment of urethral stricture - D. Yu. Pushkar (Andrologiâ i Genitalʹnaâ Hirurgiâ, 2014)
Influence of fibrin glue on results of surgical treatment of urethral stricture in experience with 32 rats and in clinic at 65 men is investigated. Glue use has led to significant reduction of operative time, tightness increase of an anastomotic seam, to reduction of catheterisation duration terms and to decrease in frequency of recurrence of urethral stricture.